PERLINDUNGAN HUKUM HAK KOMUNITAS MASYARAKAT ADAT (STUDI PERLINDUNGAN RIMBA LARANGAN MASYARAKAT ADAT RUMBIO KAMPAR - Dwi Mutia Sari; Firdaus '; Dasrol ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2018)
Customary law is part of the law which is derived from the customs, ie social rules that are created and maintained by the legal functionaries and intended to regulate legal relations in a society and have sanctions. The 1945 Constitution of Indonesia concerning on customary law has stipulated in Article 18B paragraph (2), the article states that "The State recognises and respects traditional communities along with their traditional customary rights as long as these remain in existence and are in accordance with the societal development and the principles of the Unitary State of the Republic of Indonesia, and shall be regulated by law". Besides of being protected in the constitution, protection of the rights of indigenous peoples is also regulated in several laws. Rimba larangan is the source of life for the Rumbio indigenous people, and its utilization is done hereditary. The existence of customary forests determines the social economy of the Rumbio community. Recognition is the basic fundamental needed by indigenous peoples to secure the rights of indigenous peoples. The purposes of the author of this thesis, namely: First, To find out why the Rimba Larangan as the rights of Rumbio indigenous peoples not get the recognition from the state. Secondly, to know the mechanism of protecting the rights of indigenous peoples of Rumbio towards Rimba Larangan. Thirdly, to know the efforts to be made so that the rights of indigenous peoples of Rumbio to the Rimba Larangan gain recognition from the state. This type of research can be classified in the type of sociological research, because in this study the authors directly conduct research on the location or place studied in order to provide a comprehensive and clear picture of the problem. This research conducted at Rimba Larangan Adat Rumbio Kampar Regency, while population and sample are all parties related to the problem studied in this research. The source of data using primary data, secondary data, and tertiary data. In addition, the methods of data collection in this research are by questioning through questioner, interviewing and literature studies. From the result of the research, it can be concluded that, there is a dissonance and no harmonization of the Law and Regulation related to the definition of customary forest and indigenous people, The Government considered less attention to the aspirations of indigenous peoples related to the recognition of indigenous peoples' rights toward Rimba Larangan also have to form the cooperation between indigenous and the government in terms of recognition and protection of the rights of indigenous communities. Suggestions to be given are that indigenous peoples should filed a petition in accordance with procedures which has regulated by the law and Government as a bridge to realize the aspirations of the community should provide socialization and knowledge of the Legislation Regulation related to the rights of indigenous peoples. Keywords: Legal Protection - Community Rights - Indigenous Peoples - Rimba Larangan